Analisa dan Perancangan Jaringan Berbasis VPN Pada PT. Finroll - Kerta, Johan Muliadi; Wennoris, David; Gunawan, Tonny; Erny, Erny (Bina Nusantara University, 2010)
Along with the development of the company to run operations such as data communication and perform other transactions to relations and vice versa, PT Finroll just uses the public network such as sending email to their partners. Data information is not safe in public because it can be tapped or intercepted by unauthorized person. With the Virtual Private Network (VPN), PT Finroll can do business in secure environment to their partners. The methodologies used in this research are data collection that was started by surveying, interviewing, and analyzing the current network topology, performance and design requirements that support network design. From these results, PT Finroll can increase productivity and performance from competition in their business. In addition, with this research company has a better ability to increase their competitiveness in present and the future.